2015
DOI: 10.3727/096368914x685429
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Cell Therapies to the Clinic: Characteristics of Cell Suspensions in Large-Diameter Injection Cannulae

Abstract: With the use of cell replacement therapies as a realistic prospect for conditions such as Parkinson's and Huntington's diseases, the logistics of the delivery of cell suspensions to deep brain targets is a topic for consideration. Because of the large cannulae required for such procedures, we need to consider the behavior of cell suspensions within the cannulae if we are to ensure that the injected cells are distributed as intended within the target tissue. We have investigated the behavior of primary embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Material employed for construction of delivery device Recent studies have shown that cells may be retained in the delivery device, 60 , 75 with this effect being more pronounced in glass cannulas than in metal. 75 Whether the adherence of the cells to the walls of the syringe/cannula is due to chemical, physical or charge effects has not been studied, but all of these might possibly be manipulated to decrease adhesion and settling. 75 In addition, coating the inner surface of the needle/catheter with proteins may reduce cell adhesion to the device.…”
Section: Cells As Therapeutic Agents: Translational Barriers In Neuromentioning
confidence: 99%
See 2 more Smart Citations
“…Material employed for construction of delivery device Recent studies have shown that cells may be retained in the delivery device, 60 , 75 with this effect being more pronounced in glass cannulas than in metal. 75 Whether the adherence of the cells to the walls of the syringe/cannula is due to chemical, physical or charge effects has not been studied, but all of these might possibly be manipulated to decrease adhesion and settling. 75 In addition, coating the inner surface of the needle/catheter with proteins may reduce cell adhesion to the device.…”
Section: Cells As Therapeutic Agents: Translational Barriers In Neuromentioning
confidence: 99%
“… 75 Whether the adherence of the cells to the walls of the syringe/cannula is due to chemical, physical or charge effects has not been studied, but all of these might possibly be manipulated to decrease adhesion and settling. 75 In addition, coating the inner surface of the needle/catheter with proteins may reduce cell adhesion to the device. 76 In addition to possible adherence to device materials, cells may encounter residual trace amounts of manufacturing agents that could induce apoptosis or undesired differentiation.…”
Section: Cells As Therapeutic Agents: Translational Barriers In Neuromentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported the effects of cell injection by a needle or cannula on the viabilities of embryonic rat brains cells (Torres et al, 2015), fibroblasts (Amer, et al, 2015), mesenchymal stem cells (Agashi, et al, 2009;Heng et al, 2009;Walker et al, 2010;Mamidi et al, 2012;Amer, et al, 2016), neural stem cells (Rossetti et al, 2015) and hepatocytes (Meyburg et al, 2009a). Improvement of cell injection is desirable to increase the quantities of functional live cells delivered to the target organ, and mechanistic investigation of the phenomena may facilitate development of the cell injection process.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, technical aspects of cellular delivery must be further resolved to optimize future clinical applications. 2 Numerous procedural factors determine the successful targeting of cells and biological agents into the nervous system, including cannula material and shape, 32,61,72 cell suspension vehicle, 51 cell density, 51 injection rate, 32 injection volume, 19 and tissue compliance at the injection site. 18 These parameters must be accounted for and evaluated in future preclinical studies of interneuron transplantation.…”
Section: Fig 3 Transplanted Interneurons Form Functional Inhibitorymentioning
confidence: 99%